Zonisamide Enhances Motor Effects of Levodopa, Not of Apomorphine, in a Rat Model of Parkinson’s Disease - Haruo Nishijima; Yasuo Miki; Shinya Ueno; Masahiko Tomiyama (Parkinson's Disease)
Zonisamide is a relatively recent drug for Parkinson’s disease. Multiple hypotheses have been proposed to explain the antiparkinsonian effects of zonisamide. However, it is still unclear whether the effect of zonisamide is mainly due to dopaminergic modification in the striatum, or if zonisamide works through nondopaminergic pathways. We conducted the present study to determine the mechanism that is mainly responsible for zonisamide’s effects in Parkinson’s disease. We examined the effects of zonisamide on motor symptoms in a hemiparkinsonian rat model when administered singly, coadministered with levodopa, a dopamine precursor, or apomorphine, a D1 and D2 dopamine receptor agonist. We used 6-hydroxydopamine-lesioned hemiparkinsonian rats, which were allocated to one of five groups: 14 rats received levodopa only (6 mg/kg), 12 rats received levodopa (6 mg/kg) plus zonisamide (50 mg/kg), six rats received apomorphine only (0.05 mg/kg), six rats received apomorphine (0.05 mg/kg) plus zonisamide (50 mg/kg), and six rats received zonisamide only (50 mg/kg). The drugs were administered once daily for 15 days. We evaluated abnormal involuntary movement every 20 min during a 3 h period following the injection of drugs on treatment Days 1, 8, and 15. Western blot analyses for dopamine decarboxylase and vesicular monoamine transferase-2 were performed using striatal tissues in the lesioned side of rats in the levodopa only group (n = 6) and levodopa plus zonisamide group (n = 4). Levodopa-induced abnormal involuntary movement was significantly enhanced by coadministration of zonisamide. In contrast, zonisamide had no effect on apomorphine-induced abnormal involuntary movement. Zonisamide monotherapy did not induce abnormal involuntary movement. Zonisamide did not affect striatal expression of dopamine decarboxylase or vesicular monoamine transferase-2. In conclusion, zonisamide appears to generate its antiparkinsonian effects by modulating levodopa-dopamine metabolism in the parkinsonian striatum.